The Attention to Community Security in light of the Sunnah - Adam, Zeinab Mokhtar Ahmed (Arab Journal for Sciences and Research Publishing, 2017)
Social security is one of the most important and important factors in the life of the individual and society. It is for the greatest of the divine blessings, and whoever recites the texts of the Holy Quran and the Sunnah is aware of the existence of an integrated theory with three axes: the socialization of the members of the community by virtues and their abandonment of vices, And the enactment of punitive legislation against those who are out of the legitimacy of social security to protect society and bring them back to a serious truth. And I believe that the necessity of rooting knowledge and its response to the correct sources of the book and the Sunnah, I saw that I address this subject in the light of the Sunnah and in the light of the conversations contained in it with the graduation of these conversations and comment on them at the same time showing all the issues that branch out of it as the definition of security and the importance and how it constitutes one of the life necessities as a cornerstone of our societies, and the main factor in the protection of its achievements and the path to its advancement and progress, and that its importance was coupled with the grace of life, both of the most important reasons to enable the worship of God.
Keywords: security; society; the Sunnah; legislation